Pesticide residues in bayberry (Myrica rubra) and probabilistic risk assessment for consumers in Zhejiang, China - Gui-ling YANG; Wen WANG; Sen-miao LIANG; Yi-jun YU; Hui-yu ZHAO; Qiang WANG; Yong-zhong QIAN (Journal of Integrative Agriculture, 2017)
As pesticide residues in bayberry has raised serious concern from the public in China, a monitoring survey was carried out during 2013–2014 and 157 samples were analyzed in total. Twenty-three pesticides were detected among the 44 pesticides analyzed and at least one pesticide was detected in 63% of 99 samples. Whereas 45.6% of samples were found with two or more pesticide residues, and 23.6% of samples with four or more pesticide residues. Probabilistic risk assessments indicated that estimated daily intake (EDI) of cyhalothrin at the P97.5th percentile level is 1.11 times larger than the acceptable daily intake (ADI) for children, the estimated short-term intake (ESTI) at the P97.5th percentile level is 1.9 and 1.78 times larger than the acute reference dose (ARfD) for adult and children, respectively, indicating the potential risk concern from pyrethroids. EDI of the pesticides with anti-androgenic effects ranged from 0.15–2.46 of ADI, the probability of exposure exceeding the ADI was 7.1 and 31.1% for adults and children, respectively, the probability of exposure of pyrethroids exceeding the ADI was 3.8% for children. Exposures for other pesticides and groups were below 1.0. Because the co-occurrence of frequency of cyhalothrin and cypermethrin was 9.55%, the combinations of pesticides detected with anti-androgenic effects has not been found in the present monitoring, the results indicate that the pesticide residues in bayberry will not constitute serious public health risk, however, they are significant for the management of pesticide use on bayberry and dietary health risk in China.